KETERGANTUNGAN EKONOMI AFRIKA DALAM SISTEM KEUANGAN INTERNASIONAL: PERAN PAN-AFRICAN PAYMENT AND SETTLEMENT SYSTEM (PAPSS) DALAM PENGUATAN KEDAULATAN MONETER - nur haplah, nadiya; Nurul Rahmawati; Talitha Nabilah; Fitri Dizkrayah (Lobi, 2026)
Africa's economic dependence is a structural problem that has been eliminated since the colonial era and persists through the dominance of primary commodity trade and the use of the US dollar in international transactions. This dependence limits monetary sovereignty and increases the economic vulnerability of African countries. This study aims to analyze the historical roots of Africa's economic dependence and the role of the Pan-African Payment and Settlement System (PAPSS) as an instrument of dedollarization and regional financial integration. The research method uses a qualitative descriptive approach through literature review. The analysis shows that PAPSS has the potential to reduce transaction costs, suppress exchange rate volatility, and strengthen Africa's monetary stability, despite still facing structural and geopolitical challenges.